2014
DOI: 10.1186/1749-8090-9-102
|View full text |Cite
|
Sign up to set email alerts
|

Aortic stiffness as a marker of cardiac function and myocardial strain in patients undergoing aortic valve replacement

Abstract: BackgroundCardiac function and myocardial strain are affected by cardiac afterload, which is in part due to the stiffness of the aortic wall. In this study, we hypothesize that aortic pulse wave velocity (PWV) as a marker of aortic stiffness correlates with conventional clinical and biochemical markers of cardiac function and perioperative myocardial strain in aortic valve replacement (AVR).MethodsPatients undergoing AVR for aortic stenosis between June 2010 and August 2012 were recruited for inclusion in this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 25 publications
2
12
0
Order By: Relevance
“…20) The second study (n = 12 patients) demonstrated that AVR in patients with AS was related with progressive improvement in similar 1-year aortic stiffness values comparable to that matched controls. Since the above aforementioned studies did not use PWV, our study is of clinical importance supporting the results of Kidhera et al, which found AVR has no effect on aortic stiffness 12,19 Our study indicates that PWV values correlated positively with mean aortic gradient and negatively with the AVA index preoperatively consistent with the results of study of Liu et al 11) By indicating this relation, our study advocates that AS and aortic stiffness are reflective of distinct spectrum of the same atherosclerotic disease. Unfortunately, due to relatively small sample size and different methodological assessments between our and previous studies, a larger study is needed to make a postoperatively.…”
Section: Discussionsupporting
confidence: 82%
“…20) The second study (n = 12 patients) demonstrated that AVR in patients with AS was related with progressive improvement in similar 1-year aortic stiffness values comparable to that matched controls. Since the above aforementioned studies did not use PWV, our study is of clinical importance supporting the results of Kidhera et al, which found AVR has no effect on aortic stiffness 12,19 Our study indicates that PWV values correlated positively with mean aortic gradient and negatively with the AVA index preoperatively consistent with the results of study of Liu et al 11) By indicating this relation, our study advocates that AS and aortic stiffness are reflective of distinct spectrum of the same atherosclerotic disease. Unfortunately, due to relatively small sample size and different methodological assessments between our and previous studies, a larger study is needed to make a postoperatively.…”
Section: Discussionsupporting
confidence: 82%
“…Liu et al [17] found a significant association between increased aortic pressure gradient and high PWV values. By contrast, Celik et al [18] and Kidher et al [19] did not found this correlation.…”
Section: Discussionmentioning
confidence: 82%
“…Only one previous study evaluated PWV in AVR subjects showing its correlation with NYHA class both pre and post-operatively but not with proBNP and EF [19]. Other analysis from the same study found that higher PWV was correlated with poor quality of life [26] and cognitive dysfunction [27] both pre and post-operatively and that it does not correlate with post-operatively acute kidney failure, a well know surgical AVR complication [28].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Upon severe wasting diseases such as trauma, heart failure, major surgery and cancer, human body begins to require a large amount of glutamine that, if not supplemented in time, will give rise to various diseases when exhausted. 11 , 12 Therefore, we herein analyzed the influences of glutamine and valsartan on the BNP and NT-proBNP of CHF patients.…”
Section: Introductionmentioning
confidence: 99%